Japanese pickled vegetables : 129 homestyle recipes for traditional brined, vinegared and fermented pickles - Tateno, Machiko (Tokyo [Japan] ; Rutland, Vermont : Tuttle Publishing, 2019)
Nutrient-rich, inexpensive and incredibly tasty--simple homemade Japanese tsukemono (pickles) are an integral part of everyday meals in Japan. Every Japanese family has their own tsukemono recipes handed down through the generations. In Japanese Pickled Vegetables, dietician and fermented food expert Machiko Tateno has collected more than 120 easy, healthy recipes for pickled, preserved and fermented vegetables. These pickle recipes use ingredients that are easily available in the West--including asparagus, cabbage, eggplant, zucchini, tomatoes, garlic, daikon, turnips and squashes, olive oil, honey and yogurt. More adventurous cooks can try their hand at traditional Japanese pickled vegetables like burdock root, bitter gourd, lotus root and wasabi leaves. The recipes are cross-referenced by vegetable and pickling method. A chapter on regional pickling recipes and styles lets home cooks learn more about the traditional art of tsukemono in Japan--from Tokyo to rural farm villages. A section on pickling fresh seasonal vegetables helps you to make the most of your fresh garden produce, while another provides recipes using fermented seasonings--such as Garlic Miso and Green Peppercorn that can be used to enhance the umami flavor of any dish! An important part of Japanese cuisine, Japanese pickles are often made the day they are eaten, and used as side dishes, bar snacks or garnishes. Whether you have your own vegetable garden and want ways to preserve your bounty into the winter, or are just looking for healthy meal inspiration, these homemade Japanese superfood recipes are a great place to start
The basics -- Traditional recipes -- Instant pickles.
Translation of: Kichinto oishiku tsukureru tsukemono.
Includes index.
In English, translated from the Japanese.
Keywords: Pickled foods -- Japan; Pickled foods; Cooking, Japanese; Cookbooks